THE IMPLEMENTATION OF BUZZ GROUP TECHNIQUE TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Ihsan, Rodiyal (Menara Ilmu, 2019)
Abstract :Vocabulary is one of the important language elements that must be mastered. The learner who has million words, had a better chance in practicing English. Vocabulary influences the ability of students in learning English. If students have mastered vocabulary well, they can learn the elements and skills in the language easily. The aims of this research was to know to what extent using Buzz Group Technique can improve students’ vocabulary mastery, to explain factors that influenced students’ vocabulary mastery through buzz group technique. This research was an classroom action research. It was conducted in two cycles at the EighthGrade students of SMP Negeri 3 Kerincifrom February to May2018. The data of this research consisted of qualitative and quantitative data. Research findings shown that the use of buzz group technique could improve the students’ vocabulary mastery. After implementing the action, the class situation became more active and enthusiastic. The students focused on the material which was used through topic given and the activities in the classroom tend to give students with the kind of real communication situation. Statistically, the improvement of students’ vocabulary mastery was shown by the students’ the mean score of post-test I was 70 significantly showed improvement in the post test II with mean score 85,5. It indicated that the application of buzz group technique in teaching vocabulary was success. Moreover, there were some factors influenced the change of students’ vocabulary mastery by sharing their exploring idea while the buzz group taking place as follows: (a) diong buzz situation in class activity, students could be more relaxed in exchanging their knowledge (b) buzz group make them easier to do peer correction about spelling a new word. They were enthusiastic to perform the result of discussion in front of class (c) buzz group help them to explore words based on the topic given. The result of the research implies that English teachers necessary to choose the appropriate technique in teaching vocabulary. The appropriate technique to teaching vocabulary is buzz group technique. Keywords: Buzz Group,VocabularyA